2021
DOI: 10.3390/ijms222212226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EGFR on SQSTM1 Expression in Malignancy and Tumor Progression of Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is one of the most common types of malignant tumor. Sequestosome 1 (SQSTM1) serves as an adaptor of autophagy for degrading protein aggregates. The regulation of autophagy by EGFR and its clinical impacts are indicated in various types of cancer. However, the association of EGFR and SQSTM1 in OSCC is still unknown. Our results show that the expression levels of SQSTM1 and EGFR proteins are higher in tumor tissues than in the corresponding tumor-adjacent (CTAN) tissues of OSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Zhang et al elucidated that EGFR regulates the sensitivity of OSCC cells to JQ1 (an antitumor agent) through a signaling pathway [ 28 ]. In addition, another study showed that EGFR modulates the malignant mechanisms of OSCC by regulating sequestosome-1, an autophagy-related protein [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al elucidated that EGFR regulates the sensitivity of OSCC cells to JQ1 (an antitumor agent) through a signaling pathway [ 28 ]. In addition, another study showed that EGFR modulates the malignant mechanisms of OSCC by regulating sequestosome-1, an autophagy-related protein [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…CA9, CAV1, AURKA, and EGFR are the hub genes of the 10-FRDEGs model and are markers and molecular targets of poor prognosis in patients with OSCC. So far, some progress has been achieved in the investigation of the regulatory roles of AURKA and EGFR in OSCC [ 27 , 29 ].However, CA9 and CAV1 are only linked with the susceptibility and prognosis of patients with OSCC [ 45 , 46 ]. In this study, to identify novel molecular therapeutic targets for OSCC based on the 10-FRDEGs risk scoring model in OSCC, we investigated the RNA and protein expression levels and molecular functions of CA9 and CAV1.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was demonstrated that HCRP-1 overexpression inhibited EGFR phosphorylation and that EGF treatment markedly increased EGFR expression in cells, which reversed the effects of HCRP-1 overexpression. EGFR signaling is involved in the malignant process of OSCC ( 40 ) and it can therefore be hypothesized that HCRP-1 can alleviate the malignant phenotype of cells via the inhibition of EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…The migration distance of the cells was observed and quantified. The detailed protocol was described in a previous report [ 40 ].…”
Section: Methodsmentioning
confidence: 99%